2001
DOI: 10.1046/j.1524-475x.2001.00044.x
|View full text |Cite
|
Sign up to set email alerts
|

Improved airway healing using transforming growth factor beta‐3 In a rabbit model

Abstract: Laryngeal wound healing is essential following laryngotracheal surgery. Patients with poor wound healing develop poor epithelial closure and increased granulation tissue which cause a stenosis of the repaired airway. Transforming growth factor-beta3 has been shown to enhance wound healing in cutaneous wounds, but has never been used in the airway. This study utilized a rabbit laryngeal wound-healing model that has been shown to be reproducible with limited morbidity. Thirty-four rabbits underwent a cricoid-spl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
43
0

Year Published

2008
2008
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(46 citation statements)
references
References 24 publications
0
43
0
Order By: Relevance
“…Fibroblast content, vascularity, and inflammatory cell infiltration were graded as 0 for absence, 1 for occasional presence and light scattering, 2 for abundance, and 3 for confluence of cells and fibers. Epithelial regeneration was scored as 0 for no epithelium, 1 for single-layer epithelium with partial closure, and 2 for multilayer epithelium with complete closure 6 . The same pathologist who was not informed on the groups of sections, evaluated the samples histopathologic examinations.…”
Section: Methodsmentioning
confidence: 99%
“…Fibroblast content, vascularity, and inflammatory cell infiltration were graded as 0 for absence, 1 for occasional presence and light scattering, 2 for abundance, and 3 for confluence of cells and fibers. Epithelial regeneration was scored as 0 for no epithelium, 1 for single-layer epithelium with partial closure, and 2 for multilayer epithelium with complete closure 6 . The same pathologist who was not informed on the groups of sections, evaluated the samples histopathologic examinations.…”
Section: Methodsmentioning
confidence: 99%
“…In many studies, TGF-b has been delivered locally. Loewen et al [9] traumatized cricoid cartilage in rats and applied 1 µg TGF-b3 to one group and 0.18 µg TGF-b3 to another. They found that the former group showed improved epithelialization, whereas the other group showed no significant improvement.…”
Section: Discussionmentioning
confidence: 99%
“…Among the observed variables are: a) Type and age of animals used b) Subglottic scarification method c) Number of subjects in the case and control groups a) Type and age of animals used -adult rabbits of both sexes were used in our study, as is also the case for various others papers in the literature, as they present airways similar to those of human beings, are easy to handle, and less expensive than larger animals [16][17][18][19] . The subjects weighed between 1,700 and 3,250 grams.…”
Section: Discussionmentioning
confidence: 99%
“…The principle revolves around introducing deep enough local damage to reach the lamina propria and the perichondrium, as those are key factors in promoting intense inflammation and stenosis regardless of subject age and circumferential extension of the lesion 16,11,20 . c) Number of subjects in the case and control groups -the number of subjects and their distribution within the case and control groups were based in statistical results of papers published in the literature in which subglottic scarification was performed in rabbits, consequently obtaining stenosis in 50% of the subjects on average as a result of the introduced trauma 16,18,19 . Given these results, we picked two subjects for the control group and four subjects for the case group, expecting that at least in one of the two rabbits there would be exacerbated scar formation, thus enabling the evaluation of the cellulose dressing in preventing exaggerated healing.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation